Effects of sitting versus standing after an active warm-up on vertical jump performance - Strohmeyer, H. S. (The Sport Journal, 2017)
There is significant interest concerning the effect of various warm-up protocols on performance. Efforts also have focused on warm-up decrements that occur with sports that have a halftime such as soccer or wait times associated with swimming events. However, player substitutes in many sports have significant periods of inactivity after the warm-up prior to their entry into competition. In some sports, the practice is for players to sit when not in the game, while other sports have substitutes stand. The evidence to determine if there are differences in performance based on sitting versus standing is lacking. Therefore, the purpose of this study was to compare the effects of standing versus sitting over time on vertical jump performance after an active warm-up period. Thirty-five participants participated in three different testing sessions where they were to stand, sit, or continue exercising after their warm-up. Treatment order was randomly assigned. Following warm-up, baseline standing vertical jump data for that testing session was collected. Standing vertical jump performance was then tested every 10 minutes for an hour to track performance degradation for a total of seven vertical jumps each session. Repeated measures found no differences at baseline or 10 minutes across conditions. However, there were significant differences at 20, 30, 40, 50, and 60 minutes with the vertical jump performances for the exercise condition better than the sitting or standing conditions. No differences in vertical jump performances were found between sitting and standing trials. While there are other measures to consider, these findings failed to find differences between sitting and standing on vertical jump performances after an active warm-up.